2008
DOI: 10.1088/1367-2630/10/12/125010
|View full text |Cite
|
Sign up to set email alerts
|

Strength through structure: visualization and local assessment of the trabecular bone structure

Abstract: Abstract. The visualization and subsequent assessment of the inner human bone structures play an important role for better understanding the disease-or drug-induced changes of bone in the context of osteoporosis giving prospect for better predictions of bone strength and thus of the fracture risk of osteoporotic patients. In this work, we show how the complex trabecular bone structure can be visualized using µCT imaging techniques at an isotropic resolution of 26 µm. We quantify these structures by calculating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 34 publications
(38 reference statements)
0
32
0
Order By: Relevance
“…For our study we chose 17 specimens of young (50 < age < 70) patients with high maximum compressive strength (MCS > 70 Newton (N)) out of a data set (Räth et al, 2008) of 151 cylindrical specimens with a diameter of 8 mm and a length of 14 mm, which were harvested from 73 thoracic and 78 lumbar human vertebrae. The resulting µCT grey-value images with isotropic spatial resolution of 26 µm were segmented using a low-pass filter by convolving the image with a Gaussian kernel with standard deviation 0.8 and support of 1 to remove noise and a fixed global threshold equal to 22% of the maximal grey value to extract the mineralised bone phase (Hildebrand et al 1999).…”
Section: The Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…For our study we chose 17 specimens of young (50 < age < 70) patients with high maximum compressive strength (MCS > 70 Newton (N)) out of a data set (Räth et al, 2008) of 151 cylindrical specimens with a diameter of 8 mm and a length of 14 mm, which were harvested from 73 thoracic and 78 lumbar human vertebrae. The resulting µCT grey-value images with isotropic spatial resolution of 26 µm were segmented using a low-pass filter by convolving the image with a Gaussian kernel with standard deviation 0.8 and support of 1 to remove noise and a fixed global threshold equal to 22% of the maximal grey value to extract the mineralised bone phase (Hildebrand et al 1999).…”
Section: The Data Setmentioning
confidence: 99%
“…We calculate isotropic and anisotropic scaling indices (SIM) (Räth & Morfill 1997;Monetti et al 2004;Müller et al 2006;Räth et al 2008) as measures to characterize the complex trabecular network and its degree of alignment relative to a preferential direction. Generally, scaling indices represent one way to estimate the local scaling properties of a ndimensional point set.…”
Section: Isotropic and Anisotropic Scaling Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…This method, which is a variant of the Scaling Index Method Monetti et al, 2003;Müller et al, 2006), differs from previous approaches where only an average global directionality on images was considered (Monetti et al, 2004). Recently, the SIM has been applied to µ-CT images of trabecular bone (Monetti et al, 2007;Räth et al, 2008;Monetti et al, 2009) where it was demonstrated that the use of directional information allows identifying the most important load-bearing bone substructures. As shown below, any suitable method to estimate directions in 2D or 3D can be coupled to this structure characterization procedure.…”
Section: Local Anisotropic Structure Analysismentioning
confidence: 99%
“…In our present paper we use specimens of cancellous bone as a typical example of such a tissue. We base our numerical analysis on 151 µCT images of trabecular network taken from the human vertebrae as previously described in Räth et al, 2008. The scans were acquired for the central 6 mm in length of the specimen using a µCT scanner (Scanco Medical, Bassersdorf, Switzerland).…”
Section: Trabecular Bonementioning
confidence: 99%